An exploration of socio-cultural and organizational factors affecting women's access to educational leadership - Korkor Owusu, Patrick (2014)
Recent global reports indicate that women have made tremendous improvements in educational enrolment and labour participation but are woefully underrepresented in top leadership positions. Moreover, studies have shown that feminine leadership strategies are embraced but leadership is still perceived as a prerogative of men in many societies. This study therefore sought to explore the socio-cultural and organizational factors influencing the underrepresentation of women in educational leadership within the Ghanaian cultural context. It also aimed at finding possible strategies for increasing the number female educational leaders in Ghana. The qualitative case study research method was employed for the realization of the purpose of the study. Four female principals, two female teachers, two male teachers, and one officer of an education directorate were purposefully sampled to respond to semi-structured interview questions. The data were analyzed through a data-driven qualitative content analysis and a descriptive approach was used to present the results. The study revealed some factors which hinder women’s access to leadership and also hamper their interest in leadership. Prominent among these factors include: obnoxious cultural beliefs and practices, low educational attainment, gender role socialization, some inherent characteristics of women, inflexible organizational rules and regulations, and a lack of stronger ethical leadership at the top leadership of Ghana Education Service. Moreover, the study found that Ghanaian women enact transformational ethical leadership suitable for dealing with educational challenges and improving educational outcomes. Androgynous socialization, prioritization of girl child education, cultural modernization, improvement in the local economy and social infrastructures, among other things, were suggested as ways forward towards bridging the gender gap in educational leadership in Ghana. Finally, I contend that the present educational needs of Ghana require human-oriented ethical leadership strategies which are abound in women. Women’s biological and social roles serve as the basis for the acquisition of such leadership qualities.